Inflammatory pseudotumor after ceramic-on-ceramic total hip arthroplasty - Joshua Campbell, MD; Sean Rajaee, MD; Earl Brien, MD; Guy D. Paiement, MD (Arthroplasty Today, 2017)
We present a unique case of a symptomatic adverse local tissue reaction in a patient with a ceramic-on-ceramic total hip bearing surface. To our knowledge, this pathological finding has not yet been described in a ceramic-on-ceramic articulation without a cobalt-chromium alloy trunnion or modular neck component as a source of metal wear. We conclude that despite its mechanical mostly benign wear characteristics, ceramic wear debris is not entirely inert and may lead to the development of adverse local tissue reaction.